Some remarks on the taxation of agriculture in Poland in the context of the European Green Deal - Bieluk, Jerzy (Przegląd Prawa Rolnego, 2021)
The aim of the considerations is an attempt to define the role that the system of taxation of agriculture could play in the implementation of new solutions aimed primarily at minimising the impact of agricultural production on the environment. The considerations should also take into account the role of the agricultural taxation system in shaping the systemic model of agriculture based on family farms. In conclusion, the author proposes, among other things, that the system of taxation should be directed towards easing fiscal burdens of family farms oriented towards the type and methods of production which are closest to climate neutrality. The greening of agricultural taxation ought to be one of the objectives of the reform of agricultural taxation. It should be up to the legislator, in the framework of public consultations, to define the boundary between a model individual holding which is treated preferentially, and a large-scale agricultural production that has a very negative impact on the climate.